The Influence of Flexible Working Arrangements and Emotional Intelligence on Work-Life Balance in Generation Z with Digital Literacy as a Mediating Variable - Ni Made Pula Kitasari; Nyoman Sri Subawa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the influence of flexible working arrangements (FWA) and emotional intelligence (EI) on work-life balance (WLB) among Generation Z employees in Bali's hospitality sector, with digital literacy (DL) as a mediating variable. Using a quantitative causal design, data were collected from 360 respondents through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that FWA and EI each have a positive and significant direct effect on both WLB and digital literacy. Digital literacy is also confirmed to positively and significantly influence WLB. Furthermore, digital literacy significantly mediates the relationship between FWA and WLB, as well as between EI and WLB. These findings suggest that work flexibility and emotional competence not only directly enhance employees' life balance but also indirectly do so by strengthening their digital capabilities. Hospitality organizations in Bali are therefore encouraged to integrate flexible work policies with structured digital literacy and emotional intelligence development programs as a comprehensive strategy to improve the well-being and productivity of Generation Z workers.